Loan Loss Provisioning in Banking — A Dynamic Counter-cyclical Approach to Buffer Losses in China - Wang, Yu-Sheng (2017)
Loan loss provisions (LLPs) were first introduced in 1986 to serve as a defence against the credit risk by banks. They are founded on the basis of future loss predictions on loan portfolios from banks. LLPs are currently very important to banks’ continuous operations, and global policy makers have crucial concerns about the effects of LLPs on lending strategy. In China, the loan loss provisioning system has been in operation since 1988. The system has received constant expansion and improvement due to various reforms. A new set of regulatory stipulations were put forward by the authorities to ameliorate Chinese LLPs. The aim is to keep pace with similar regulatory systems worldwide whilst accommodating China’s basic conditions on a national level. Through these regulatory improvements, banks’ profits (after pre-tax deduction) as well as the liquidity and safety of their assets are ensured.